Hydrogels of Cytoskeletal Proteins Preparation, Structure, and Emergent Functions - Osada, Yoshihito; Kawamura, Ryuzo; Sano, Ken-Ichi (Springer International Publishing : Imprint: Springer, 2016)
This book describes a new family of bio-polymer gels made from cytoskeletal proteins - actin, microtubule, and tropomyosin. The importance of the gel state with multi-scale hierarchical structure is emphasized to utilize emergent functions in living organisms. Detailed protocol of gel preparation, specified method of structure investigation, and dynamic studies of self-organization, self-healing, synchronized oscillating, and autonomous motility functions are introduced together with biomimetic functions of synthetic hydrogels.